Laser powder bed fusion of Ti-6Ta-1.5Zr-0.2Ru-5Cu (mass%) – process parameter evaluation using single tracks analysis - Phala Ngwakoana; Polese Claudia; Ciftci Jakub; Choma Tomasz; Cornish Lesley (MATEC Web of Conferences)
Printing of single tracks from atomised powder was carried out to determine the potential parameters for Laser Powder Bed Fusion of Ti- 6Ta-1.5Zr-0.2Ru-5Cu (mass%). Parameters that were varied included laser power, scanning speed, beam diameter, linear and planar energy density. The single tracks were characterised by SEM and SEM-EDX, showing variations in microstructural homogeneity. Promising tracks were produced using laser power of 157.5 W, scanning speed of 600 mm/s, beam diameter of 0.15 mm, 0.263 J/mm linear energy and 1.750 J/mm2 planar energy density. XRD for one of these tracks indicated (αTi) and (βTi) solid solutions as well as the Ti2Cu phase.